2023
DOI: 10.3389/fevo.2023.1073775
|View full text |Cite
|
Sign up to set email alerts
|

Are fungicides a driver of European foulbrood disease in honey bee colonies pollinating blueberries?

Abstract: IntroductionBlueberry producers in Canada depend heavily on pollination services provided by honey bees (Apis mellifera L.). Anecdotal reports indicate an increased incidence of European foulbrood (EFB), a bacterial disease caused by Melissococcus plutonius, is compromising pollination services and colony health. Fungicidal products are commonly used in blueberry production to prevent fungal diseases such as anthracnose and botrytis fruit rot. Pesticide exposure has been implicated in honey bee immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Viral infections were also investigated by Fowler and colleagues ( 2024 ), as part of their investigation into European foulbrood (EFB; causative agent Melissococcus plutonius ). They found that viral coinfections and hygienic behavior did not correlate with the presence of EFB infection, suggesting other drivers may be responsible for observed outbreaks, particularly those noted during blueberry pollination ( Grant et al 2021 , Thebeau et al 2023 ).…”
Section: Abiotic and Biotic Honey Bee Stressorsmentioning
confidence: 99%
“…Viral infections were also investigated by Fowler and colleagues ( 2024 ), as part of their investigation into European foulbrood (EFB; causative agent Melissococcus plutonius ). They found that viral coinfections and hygienic behavior did not correlate with the presence of EFB infection, suggesting other drivers may be responsible for observed outbreaks, particularly those noted during blueberry pollination ( Grant et al 2021 , Thebeau et al 2023 ).…”
Section: Abiotic and Biotic Honey Bee Stressorsmentioning
confidence: 99%
“…Blueberry pollination contracts are an important source of income for beekeepers (Bixby et al 2023). However, some beekeepers and researchers have raised concerns that colony health deteriorates after engaging in highbush blueberry pollination (Wardell 1982, Higo et al 2019, Thebeau et al 2022, Thebeau et al 2023). Several sources have postulated that European foulbrood (EFB, caused by Melissococcus plutonius ), exposure to fungicides, nutritional deficits, and their interactions could be the underlying causes of poor colony health outcomes perceived to be associated with highbush blueberry pollination (Wardell 1982, Graham et al 2021, Graham et al 2022, Thebeau et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Fungicides and their adjuvants (non-active ingredients that enhance pesticide performance, such as surfactants) can increase honey bee susceptibility to pathogens, such as Vairimorpha ceranae (a microsporidian parasite, formerly known as Nosema ceranae (Tokarev et al 2020)) (Pettis et al 2013), viruses (Degrandi-Hoffman et al 2015, Fine et al 2017, O’Neal et al 2019), and, in some cases, M. plutonius (Thebeau et al 2023). Although honey bees can also be exposed to fungicides and other agrochemicals while foraging on non-blueberry plants (Pettis et al 2013, Graham et al 2022), these interactions between fungicides and pathogens broadly highlight the utility of analyzing multivariate pathogen responses in crop exposure trials.…”
Section: Introductionmentioning
confidence: 99%